1994
DOI: 10.3109/00016349409006278
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis and cervical intraepithelial neoplasia

Abstract: The possibility exists that bacterial vaginosis is in some way associated with the development of cervical intraepithelial neoplasia, i.e. as a cofactor to human papilloma virus. Therefore, bacterial vaginosis must be taken in consideration in future studies on CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 19 publications
1
56
0
1
Order By: Relevance
“…17 These opportunistic agents would be favored by imbalances in the vaginal flora. 18 According to Edwards, 1 Escherichia coli was the species most associated with bacterial vaginitis, although in the present series, it was found that Staphylococcus aureus was the agent most frequently causing it. Vaginal infections due to Bacteroides sp., Peptostreptococcus sp., Prevotella sp.…”
Section: Discussionmentioning
confidence: 55%
“…17 These opportunistic agents would be favored by imbalances in the vaginal flora. 18 According to Edwards, 1 Escherichia coli was the species most associated with bacterial vaginitis, although in the present series, it was found that Staphylococcus aureus was the agent most frequently causing it. Vaginal infections due to Bacteroides sp., Peptostreptococcus sp., Prevotella sp.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies which have examined the relationship between BV and cervical intraepithelial neoplasia (CIN) gave conflicting conclusions with different results which ranged from a strong association [1] to no association at all [2]. In the earlier eighties Pavić [3], discussing possible analogies between gastric and cervical cancer, concluded that in both, an elevation of pH could encourage proliferation of bacteria, and those situation could be preceded by epithelial metaplasia and dysplasia.…”
mentioning
confidence: 99%
“…Because of the improper use of OTC antifungal medications, the vaginal microflora may be altered 26 and opportunistic infections such as BV may go unchecked and untreated. Vaginitis, in particular BV, has been associated with increased risk of serious obstetric and gynecologic complications and disorders [27][28][29][30][31] . Since the patient is advised to see her doctor/ healthcare provider when the test is positive (pH > 4.5), a false-positive test would only cause the symptomatic patient to visit her healthcare provider for proper diagnosis of an abnormal condition.…”
Section: Discussionmentioning
confidence: 99%